Integrating Affective–Spiritual Assessment in Education: Instrument Development and Implementation - Dewi, Mira Novia; Masritawati, Masritawati; Fatimah, Nurhayati; Asma, Siti (El-Rusyd, 2025)
Assessment functions as a method for evaluating students’ development after the learning process takes place. In the field of education, institutions need to design and develop assessment instruments that accurately measure affective–spiritual aspects so that learning objectives can be achieved optimally, considering that these aspects play an important role in determining an individual’s success. This study aims to describe the process of developing an affective–spiritual assessment instrument used in the learning process. The method employed is research and development (R&D), which consists of three main stages: observation, self-assessment, and attitude assessment. The results show that the presence of an affective-spiritual evaluation instrument is essential for shaping students’ behavior both within the school environment and in the wider community. The implications of this study indicate that developing appropriate assessment instruments can enhance the effectiveness of the educational process and support comprehensive character development among students.